2021
DOI: 10.3390/ani11020306
|View full text |Cite
|
Sign up to set email alerts
|

Dry Matter Intake and In Vivo Digestibility of Grass-Only and Grass-White Clover in Individually Housed Sheep in Spring, Summer and Autumn

Abstract: Intake and digestibility are key drivers of animal production from grazed forage. The objective of this study was to compare the in vivo digestibility and voluntary dry matter (DM) intake of grass-only and grass-white clover (grass-clover) forage in individually housed sheep. This study was a Latin square design, repeated on three occasions in 2017: Spring (27 March–29 April), summer (19 June–22 July) and autumn (4 September–29 September). Grass-clover and grass-only swards were harvested daily and offered ad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…The low DM content of some prewilted grass samples (≤300 g kg −1 DM) was associated with grass harvested in autumn (after October 20). In this period, wet mowing conditions make it difficult to efficiently wilt the harvested grass and to attain a sufficient DM content (Hurley et al, 2021; Larsen et al, 2016). Overall, silages with less than 25% DM are at risk of juice losses and poor fermentation, while those with more than 45% DM face challenges in proper compaction, leading to increased oxygen presence and potential mold and yeast development (Kung et al, 2003; Muck, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The low DM content of some prewilted grass samples (≤300 g kg −1 DM) was associated with grass harvested in autumn (after October 20). In this period, wet mowing conditions make it difficult to efficiently wilt the harvested grass and to attain a sufficient DM content (Hurley et al, 2021; Larsen et al, 2016). Overall, silages with less than 25% DM are at risk of juice losses and poor fermentation, while those with more than 45% DM face challenges in proper compaction, leading to increased oxygen presence and potential mold and yeast development (Kung et al, 2003; Muck, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of experiments have demonstrated that immature perennial ryegrass (PRG) can be highly digestible (Morgan & Stakelum, 1987;Beecher et al, 2014Beecher et al, , 2018Garry et al, 2020Garry et al, , 2021. The inclusion of white clover into PRG swards has been demonstrated to further increase the in vivo OMD of pasture-based diets (Peyraud, 1993;Hurley et al, 2021). This high OMD of immature pasture results in high concentrations of metabolisable or net energy per kg of dry matter (DM) (Bruinenberg et al, 2002; Institut National de Recherche Agronomique [INRA], 2018).…”
Section: Quantifying the Nutritive Value Of Pasturementioning
confidence: 99%
“…The chemical composition of herbage varies during the growing season. Autumn herbage, in comparison to spring herbage, has less sugar and fibre and a higher crude protein (CP) and fat content (Hurley et al, 2021; Larsen et al, 2016). In the temperate climate of Belgium, the herbage season approaches its end in October.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the wet autumn mowing conditions make it difficult to wilt autumn herbage to the desired dry matter (DM) content. Both factors jeopardize the palatability of the silage and result in lower uptake by cattle (Hurley et al, 2021; Larsen et al, 2016). Improving the protein quality of autumn herbage may be a promising strategy on dairy farms for two reasons.…”
Section: Introductionmentioning
confidence: 99%